Psoriasis vulvae - Jarošová, Lucie; Driák, Daniel; Sehnal, Borek; Kacerovská, Denisa (Ceska gynekologie, 2022)
OBJECTIVE: Case presentation, differential dia-gnostic, possible therapeutic procedure and a brief literature report. CASE REPORT: An 84-year-old woman was repeatedly examined for chronic extended dermatologic lesion on lower abdomen, external genitals, perianal region, groin and adjacent inner thighs. CONCLUSION: Neither colposcopy with dermatovenerologic consultation, nor histopathological examination led to a precise conclusion. Only a special dermatopathologic expertise showed a dia-gnosis of inverse psoriasis with suggested therapy.
Keywords: Vulvitis; vulval lesion; psoriasis; Vulva; lidé; senioři nad 80 let; Female; psoriáza; Psoriasis; vulvitida; vulva; Aged, 80 and over; ženské pohlaví; Humans